2018
DOI: 10.11113/jt.v80.10875
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Surface Roughness and Wettability of Titanium Alloy Coated by Yzp-30wt. % Tio2 for Dental Application

Abstract: Various roughness and surface topography of titanium coated ceramic material have been developed and used in clinical trials especially in a medical implant. The present work aimed to investigate the phase and microstructural of the yttria stabilized zirconia (YZP) coating reinforced titania (TiO2) and its effects on wettability for dental implant application. Plasma spray technique was used to prepare the pure YZP and YZP-30 wt.% TiO2 coatings. The titanium alloys coated with YZP/TiO2 were investigated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…Considering surface roughness and wettability in this study, increasing contact angles were observed with increased surface roughness. This data is also supported by Afida Jemat et al’s comparison of 3 biomaterials which showed that increased contact angles can also be found with higher surface roughness ( Jemat et al, 2018 ). Yu-Hua Pan et al, also showed in a comparison between control and GDP-treated zirconia disks that increased surface roughness is associated with higher contact angle ( Pan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 70%
“…Considering surface roughness and wettability in this study, increasing contact angles were observed with increased surface roughness. This data is also supported by Afida Jemat et al’s comparison of 3 biomaterials which showed that increased contact angles can also be found with higher surface roughness ( Jemat et al, 2018 ). Yu-Hua Pan et al, also showed in a comparison between control and GDP-treated zirconia disks that increased surface roughness is associated with higher contact angle ( Pan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 70%
“…It was reported in a separate study that the effect of self-cleaning is the result of the twin effects of the surface roughness and hydrophobicity (Shirtcliffe et al 2010). A higher surface roughness contributed to a higher contact angle, and hence a higher hydrophobicity (Jemat et al 2013). The combined effect allowed the droplets to stay on the top of the surface and roll off together with the soil.…”
Section: Roughness and Adhesion Forcementioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) coatings are widely used in biomedical applications and self-cleaning coatings owing to their wear and corrosion resistance, and biocompatibility. [1][2][3][4] However, TiO 2 coatings have drawbacks, such as failure caused by bacterial infection in biomedical applications, 5 and TiO 2 photocatalytic activity is limited within the visible region owing to low sunlight absorption. [6][7][8] Hence, various methods have been tested to overcome this problem, including mixing with different oxides such as zirconium oxide (ZrO 2 ) and stannic oxide (SnO 2 ) to increase the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%